Platinum(II) Terpyridine Anticancer Complexes Possessing Multiple Mode of DNA Interaction and EGFR Inhibiting Activity - Li, Chaoyang; Xu, Fengmin; Zhao, Yao; Zheng, Wei; Zeng, Wenjuan; Luo, Qun; Wang, Zhaoying; Wu, Kui; Du, Jun; Wang, Fuyi (Frontiers in Chemistry, 2020)
Platinum(II) terpyridine complexes has attracted increasing attention as they have displayed great potential as antitumor agents due to their high intercalation affinity with nucleic acids. Epidermal growth factor receptor (EGFR) is often overexpressed in various tumor cells, leading to uncontrolled growth of tumor, and is regarded as an important target for developing novel antitumor drugs. Herein, we report four platinum(II) terpyridine complexes bearing EGFR inhibiting 4-anilinoquinazoline derivatives as potent multi-targeting antiproliferation agents against a series of cancer cells. EGFR inhibition assay revealed that these complexes are highly potent EGFR inhibitors. But competitive DNA binding assay and docking simulations also suggested that these complexes exhibited multiple modes of DNA interaction, especially great affinity toward DNA minor groove. Finally, cellular uptake and distribution measurements by inductively coupled plasma mass spectrometry (ICP-MS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) demonstrated that both nucleus DNA and membrane proteins are important targets for their anticancer mechanisms. The complexes herein can therefore be regarded as promising multi-targeting anticancer agents.